The Role of Women in Education to Face the Era of Society 5.0: English Language - Desak Ketut Angraeni Eni; Tri Aspiyana; Susi Susi (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Ida Sang Hyang Widhi/Ranying Hatalla Langit created men and women into this world to complement each other in living a life that continues to move forward. As we are currently facing is the life of society 5.0 where technological innovation is a solution to various problems of life today. Of course, this makes every human being, especially women, no longer underestimated by anyone. Women are able to play a role in every field of life in this world, especially in the field of education. Women, whether as housewives or working women or both, must have a good education so that they can have an impact on their children, their families and even the surrounding community for the better. Women's participation in education is also explained in the teachings of Hinduism in the holy book of Yayurvedha XIV.21. that women are the best teachers in the family, there is no difference in social treatment between men and women. Because of women too, various forms of offerings will be carried out, because of women too, tranquility and peace will be realized, therefore people who want to prosper should always respect women. But the journey of a woman in the life of society 5.0 is of course has many obstacles. Barrier that occur to women in the field of education is socio-cultural factor where there is a view in society that a woman do not need to get the higher education, because they will end up being housewives eventualy. This view makes women hesitant to dream of having a higher education and having a good career. In fact, if a woman is able to have a higher education and work, of course she can help her husband, who is the head of the family, in improving the family economy. In addition, women who have education will certainly affect the pattern of educating their children even if they choose to become housewives. Women's education affects the education of future generations because women are the first educators in the family.